rail

JP7620257B1Active Publication Date: 2025-01-23NIPPON STEEL CORPORATION
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024550787
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-10-12
Filing Date
2024-05-30
Publication Date
2025-01-23
Estimated Expiration
2044-05-30

AI Technical Summary

Benefits of technology

【0014】 本開示のレールでは、優れた耐摩耗性及び耐損傷性が得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620257000011
    Figure 0007620257000011
  • Figure 0007620257000012
    Figure 0007620257000012
  • Figure 0007620257000013
    Figure 0007620257000013
Patent Text Reader

Abstract

To provide a rail having excellent wear resistance and damage resistance. The rail (1) of this embodiment contains, by mass%, C: 0.80 to 1.20%, Si: 0.80 to 2.50%, Mn: 0.10 to 2.00%, P: 0.0250% or less, and S: 0.0250% or less, with the balance being Fe and impurities. In the metal structure of the head surface portion (10A), the pearlite area ratio is 95% or more, the Vickers hardness is 400 HV or more, and in the head surface portion (10A), the Si positive segregation degree, which is the ratio of the maximum Si concentration in the Si positive segregation band to the Si concentration in the bulk region, is more than 1.00 to 1.35, and the Si negative segregation degree, which is the ratio of the minimum Si concentration in the Si negative segregation band to the Si concentration in the bulk region, is 0.90 to less than 1.00.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to rails. [Background technology]

[0002] Economic development is driving new development of natural resources such as coal and iron ore. Specifically, mining of natural resources is progressing in previously undeveloped areas with harsh natural environments. As a result, the track environment of freight railways that transport resources is becoming harsher. For example, the curvature of curved sections is becoming smaller, and the gradient of gradient sections is becoming steeper.

[0003] As a result of the severe track environment, the stress and slippage that wheels impose on the rails are increasing. As a result, wear and damage to the rails are increasing. Therefore, there is a demand for improved wear resistance and damage resistance in rails. Against this background, development of rails with improved wear resistance and damage resistance is underway.

[0004] With the aim of improving the wear resistance of rails, rails have been proposed as disclosed in Patent Documents 1 and 2. In these rails, in order to increase the wear resistance, the lamellar spacing of pearlite is refined to increase the hardness of the steel, and the C content of the steel is increased to increase the volume fraction of cementite in the pearlite lamellae.

[0005] Specifically, in Patent Document 1, the head of a rail after rolling or the head of a reheated rail is accelerated cooled from the austenite temperature range to 850-500°C at a rate of 1-4°C / sec. This improves the wear resistance of the rail, as disclosed in Patent Document 1. In addition, in Patent Document 2, hypereutectoid steel (C: more than 0.85-1.20%) is used to increase the volume ratio of cementite in the lamellae of the pearlite structure, as disclosed in Patent Document 2. This improves the wear resistance of the rail.

[0006] Furthermore, in order to improve the damage resistance as well as the wear resistance of rails, rails disclosed in Patent Documents 3 and 4, for example, have been proposed.

[0007] In Patent Document 3, hypereutectoid steel (C: 0.73-0.85%) is used to balance the amounts of Mn and Cr, and the lamellar spacing in pearlite is made fine. This increases the hardness of the steel. Patent Document 3 discloses that this improves the wear resistance and damage resistance of the rail. Patent Document 4 also discloses that hypereutectoid steel (C: 0.70-0.85%) is used to balance the amounts of Si, Mn, and Cr, thereby controlling the amount of pearlite and bainite formed and increasing the hardness of the steel. Patent Document 4 also discloses that this improves the wear resistance and damage resistance of the rail. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Special Publication No. 63-023244 [Patent Document 2] Patent No. 3078461 [Patent Document 3] Patent No. 4390004 [Patent Document 4] Patent No. 6822757 Summary of the Invention [Problem to be solved by the invention]

[0009] The techniques disclosed in Patent Documents 1 and 2 improve the wear resistance of rails by increasing the hardness of steel by minimizing the lamellar spacing in pearlite and by increasing the volume ratio of cementite in pearlite lamellae. However, the rails disclosed in Patent Documents 1 and 2 may not provide sufficient wear resistance when used in the severe track environments that have been required in recent years.

[0010] The techniques disclosed in Patent Documents 3 and 4 improve the wear resistance and damage resistance of rails by increasing the hardness of steel by refining the lamellar spacing in pearlite or by controlling the metal structure of steel to increase the hardness. However, even the rails disclosed in Patent Documents 3 and 4 may not provide sufficient wear resistance and damage resistance when used in the severe track environments that have been required in recent years.

[0011] As described above, a rail having excellent wear resistance and damage resistance that can be used in freight railways, which have a severe track environment, has not yet been provided.

[0012] It is an object of the present disclosure to provide a rail that provides excellent wear and damage resistance. [Means for solving the problem]

[0013] The rail of the present disclosure has, in mass %, C: 0.80-1.20%, Si: 0.80-2.50%, Mn: 0.10-2.00%, P: 0.0250% or less, S: 0.0250% or less, Al: 0-1.0000%, N: 0-0.0200%, Cr: 0-1.00%, Mo: 0-0.50%, Co: 0-1.00%, B: 0. The head has a metal structure of 0.0050%, Cu: 0-1.00%, Ni: 0-1.00%, V: 0-0.200%, Nb: 0-0.0500%, Ti: 0-0.0500%, Mg: 0-0.0200%, Ca: 0-0.0200%, rare earth elements: 0-0.0500%, Zr: 0-0.0200%, and the balance is Fe and impurities. In the metal structure of the head surface portion from the head outer surface to a depth of 20 mm, the pearlite area ratio is 95% or more, and the Vickers hardness is 400HV or more. In the head surface portion, the Si positive segregation degree, which is the ratio of the maximum Si concentration in the Si positive segregation zone to the Si concentration in the bulk region, is more than 1.00 to 1.35. The degree of negative Si segregation, which is the ratio of the minimum value of the Si concentration in the negative Si segregation zone to the Si concentration in the bulk region, is 0.90 to less than 1.00. Effect of the Invention

[0014] The rails of the present disclosure provide excellent wear and damage resistance. [Brief description of the drawings]

[0015] [Figure 1A] FIG. 1A is a cross-sectional view perpendicular to the longitudinal direction of the rail of this embodiment. [Figure 1B] FIG. 1B is a cross-sectional view of the rail head area for explaining a method of defining the head surface portion in FIG. 1A. [Figure 1C] FIG. 1C is a cross-sectional view of the rail head area following FIG. 1B. [Figure 1D] FIG. 1D is a cross-sectional view of the rail head area following FIG. 1C. [Figure 1E] FIG. 1E is a cross-sectional view of the rail head area following FIG. 1D. [Figure 1F] FIG. 1F is a cross-sectional view of the rail head area following FIG. 1E. [Figure 2A] FIG. 2A is a schematic diagram showing how a crack develops near the tread surface of a rail. [Figure 2B] FIG. 2B is a schematic diagram showing the state of crack generation near the tread surface of a rail, which is different from FIG. 2A. [Figure 2C] FIG. 2C is a schematic diagram showing the state of crack generation in the vicinity of the tread surface of a rail, which is different from FIG. 2A and FIG. 2B. [Diagram 3] FIG. 3 is a perspective view of a rolling fatigue testing machine that reproduces damage caused by the rolling contact of a rail and wheels. [Figure 4A] FIG. 4A is a schematic diagram showing the relationship between the state of crack generation in the vicinity of the rail tread and the Si segregation zone. [Figure 4B] FIG. 4B is a schematic diagram different from FIG. 4A, showing the relationship between the state of crack generation in the vicinity of the rail tread and the Si segregation zone. [Figure 4C] FIG. 4C is a schematic diagram showing the relationship between the state of crack generation in the vicinity of the rail tread and the Si segregation zone, which is different from FIG. 4A and FIG. 4B. [Diagram 5] FIG. 5 is an enlarged view of the portion of the measurement surface of a test piece taken from a rail for hardness measurement, in the vicinity of the outer surface. [Figure 6]FIG. 6 is a schematic diagram for explaining how to determine the Si positive segregation degree. [Figure 7] FIG. 7 is a schematic diagram for explaining how to determine the degree of negative Si segregation. [Figure 8] FIG. 8 is a schematic diagram showing an example of a cooling device used in a heat treatment step in the manufacturing process of the rail of this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The rail of this embodiment will now be described in detail. In the following, % in the chemical composition means mass % unless otherwise specified.

[0017] [Rail configuration] 1A is a cross-sectional view perpendicular to the longitudinal direction of a rail 1 of this embodiment. Referring to FIG 1A, the rail 1 includes a rail head portion 10, a bottom portion 15, and a post portion 14. The rail head 10 refers to the portion of the rail 1 above the narrowed portion at the center in the height direction. The rail head 10 receives the load from the wheels of the railway vehicle. The bottom 15 is fixed to the sleeper. The bottom 15 supports the rail head 10, which receives the load from the wheels, via the pillar portion 14. The pillar portion 14 is disposed between the rail head 10 and the bottom portion 15. The upper end of the pillar portion 14 is connected to the rail head 10, and the lower end of the pillar portion 14 is connected to the bottom portion 15.

[0018] The rail head 10 includes a top portion 11, a pair of head corner portions 12 (12L and 12R), and a pair of lower jaw portions 13. The top portion 11 is located at the center of the rail head 10 in the width direction. The pair of head corner portions 12 (12L and 12R) are located at both ends of the top portion 11 in the width direction of the rail head 10. In other words, the top portion 11 is located between the pair of head corner portions 12 (12L and 12R). In a cross-sectional view perpendicular to the longitudinal direction of the rail 1, the head corner portion on the left side of the top portion 11 is referred to as the "head corner portion 12L," and the head corner portion on the right side of the top portion 11 is referred to as the "head corner portion 12R." The head corner portions 12L and 12R are collectively referred to as the head corner portion 12. One of the pair of head corner portions 12L and 12R is a gauge corner (GC) portion that mainly comes into contact with the wheel.

[0019] In the rail head 10, the surface of the head top portion 11 that faces upward when the rail 1 is uprighted and the surfaces of the pair of head corner portions 12 are combined and referred to as the head outer surface 10S. The pair of lower jaw portions 13 are disposed on opposite sides of the pair of head corner portions 12 in the height direction of the rail 1. The pair of lower jaw portions 13 are the outer surfaces of a portion of the rail 1 that is narrowed in the center in the height direction.

[0020] The area extending from the head outer surface 10S to a depth of 20 mm is referred to as the head surface portion 10A. D1 in FIG. 1A indicates the range from the head outer surface 10S to a depth of 20 mm. The microstructure of the head surface portion 10A is made of pearlite with a Vickers hardness of 400 HV or more. This enhances the wear resistance and damage resistance of the rail 1.

[0021] Generally, the service life of a rail is about 20 mm from the head outer surface 10S. Therefore, by making the microstructure of the head surface portion 10A a pearlite structure with a Vickers hardness of 400 HV or more, the wear resistance and damage resistance of the rail 1 are ensured.

[0022] [Method of defining the area of ​​the head surface portion 10A] The head surface portion 10A is defined in the following manner. With reference to Fig. 1B, the center position of the width of the surface of the rail head portion 10 in a cross section perpendicular to the longitudinal direction of the rail 1 is defined as point P11. A line segment L11 is assumed to extend in the depth direction starting from point P11. Line segment L11 is coaxial with the normal to the head outer surface 10S at point P11, and corresponds to the center line of the rail 1 in the cross section of the rail 1.

[0023] A position on the normal line L11, 20 mm (D1) in the depth direction from point P11, is defined as point X. A line segment L100 is drawn horizontally from point X, and points A and B are the intersections between the line segment L100 and the surface of the rail head 10. With reference to Fig. 1C, the area from point A to point B on the surface of the rail head 10 of the rail 1 is divided into thirds, and the boundary positions of these thirds are designated as points C and D. With reference to Fig. 1D, the area between points C and D is defined as the head top 11. Furthermore, on the surface of the rail head 10, the central position between points A and C is designated as point E. Similarly, the central position between points B and D is designated as point F.

[0024] With reference to FIG. 1E, the central position between points A and E on the surface of the rail head 10 is defined as point G. Similarly, the central position between points B and F is defined as point H. On the surface of the rail head 10, the range between points C and G is defined as a head corner portion 12L. Note that the range between points A and G is excluded from the head corner portion 12L because this range is an area that has substantially little contact with a rail vehicle. Similarly, the range between points D and H is defined as a head corner portion 12R. The range between points B and H is excluded from the head corner portion 12R because this range is an area that has substantially little contact with a rail vehicle.

[0025] The head top 11, head corners 12L and head corners 12R are defined by the above method. Among the surfaces of the rail head 10, the surfaces of the head top 11, head corners 12L and head corners 12R, that is, the surface from point G to point H, are defined as the head outer surface 10S.

[0026] In the top portion 11, the head corner portion 12L and the head corner portion 12R, the depth direction is defined as follows. The normal direction of the head outer surface 10S is defined as the depth direction in the top portion 11. On the other hand, the depth directions of the head corner portions 12L and 12R are defined as follows. Referring to FIG. 1F, a line segment L13 which is a tangent to the lower jaw 13 L and L13 R Let us assume that the line segment L13 L and L13 R The intersection point between these two points is defined as point P13. Point P13 is located on the normal line L11. In the head corner portion 12L, the direction of a line segment connecting an arbitrary point on the head outer surface 10S (i.e., the surface between points C and G) and point P13 is defined as the depth direction at the arbitrary point. For example, if the arbitrary point is point E, the line segment L12 between point E and point P13 is defined as the depth direction at the arbitrary point. L The direction along is defined as the depth direction at point E. Similarly, in the head corner portion 12R, the direction of a line segment connecting an arbitrary point on the head outer surface 10S (i.e., the surface between points D and H) and point P13 is defined as the depth direction at the arbitrary point. For example, if the arbitrary point is point F, the line segment L12 between point F and point P13 is defined as the depth direction at the arbitrary point. R The direction along is defined as the depth direction at point F.

[0027] Based on the above definition, the line segment L at a depth of 20 mm from the head outer surface 10S between points G and H D20 By the above method, the head surface portion 10A shown in FIG. 1A can be defined.

[0028] [Technical concept of the rail 1 of this embodiment] Next, the technical concept of the rail 1 of this embodiment will be described.

[0029] The present inventors first investigated rails that provide excellent wear resistance and damage resistance from the viewpoint of chemical composition. As a result of the investigation, it was found that the rails had the following composition by mass: C: 0.80-1.20%, Si: 0.80-2.50%, Mn: 0.10-2.00%, P: 0.0250% or less, S: 0.0250% or less, Al: 0-1.0000%, N: 0-0.0200%, Cr: 0-1.00%, Mo: 0-0.50%, Co: 0-1.00%, B: 0-0.0050%, Cu: 0-1.00%, Ni: 0. The inventors considered that excellent wear resistance and damage resistance could be obtained if a rail had a chemical composition of: Nb: 0-1.00%, V: 0-0.200%, Nb: 0-0.0500%, Ti: 0-0.0500%, Mg: 0-0.0200%, Ca: 0-0.0200%, rare earth elements: 0-0.0500%, Zr: 0-0.0200%, and the balance being Fe and impurities.

[0030] The present inventors further investigated means for improving wear resistance from the viewpoint of metal structure. As a result of the investigation, the present inventors found that sufficient wear resistance can be obtained if the pearlite area ratio is 95% or more and the Vickers hardness is 400HV or more in the metal structure of the head surface portion 10A.

[0031] The present inventors further conducted research into means for improving the damage resistance of a rail having the above-mentioned chemical composition and metal structure.

[0032] The inventors investigated damage that occurs on the head surface portion 10A of a rail when it is used in a harsh environment such as a freight railway. As a result, they found that a crack occurs on the surface of the head surface portion 10A due to contact with the wheels, and the crack further propagates into the rail, causing spalling damage on the rolling surface of the rail (the surface in contact with the railway wheels). Therefore, the inventors conducted a detailed study of the behavior of crack occurrence and propagation on the head surface portion 10A. As a result, the inventors discovered the following.

[0033] 2A to 2C are schematic diagrams showing how cracks develop in the vicinity of the tread surface of the rail 1. With reference to Fig. 2A to 2C, cracks that develop in the head surface portion 10A of the rail 1 can be in the following three states. Case 1 (Fig. 2A): A large crack (initial crack CRA1) is generated linearly at a certain angle to the contact surface with the wheel 2 (head outer surface) 10S. Case 2 (Figure 2B): A large crack (initial crack CRA1) that is generated linearly at a certain angle to the contact surface 10S with the wheel 2 and a wave-shaped crack (propagating crack CRA2) that propagates from the tip of the initial crack CRA1 due to repeated contact with the wheel 2 (initial crack CRA1 + propagating crack CRA2). Case 3 (Fig. 2C): A crack (initial crack CRA1) that is generated linearly at a certain angle to the contact surface 10S with the wheel 2, but has a shallower depth D than Case 1. In the case of Case 3, where the depth D of the initial crack CRA1 is shallow, delamination damage does not occur.

[0034] Based on the above findings, the inventors further investigated the cause of crack (CRA1 and CRA2) generation by the following method. Rails with C contents of 0.80 to 1.20% were fabricated. Then, using a rolling fatigue testing machine shown in Fig. 3, the relationship between the generation behavior of large and coarse cracks immediately below the contact surface and the element distribution of the steel material constituting the rail was investigated.

[0035] [Overview of the rolling fatigue testing machine] Referring to FIG. 3, in the rolling fatigue testing machine, a rail 1 is placed on a sleeper 3. A motor 4 rotates a wheel 2. A load stabilizing device 5 holds down the wheel 2 that is rotated by the motor 4. In the rolling fatigue test, the wheel 2 is placed on the rail 1. Then, while a predetermined load is applied to the wheel 2 using the load stabilizing device 5, the wheel 2 repeatedly rolls back and forth on the rail head 10 of the rail 1 along the longitudinal direction of the rail 1.

[0036] [Rolling fatigue test conditions] The chemical composition and hardness of rail 1, the heat treatment method of rail 1, the conditions of the rolling fatigue test of rail 1 and wheel 2 to reproduce crack damage, the evaluation method for large and coarse cracks immediately below the contact surface, and the elemental analysis method of the crack initiation area in the rolling fatigue test are as shown below.

[0037] [Chemical composition, shape and characteristics of rail 1] The chemical composition of the rail 1 was, in mass%, C: 0.80 to 1.20%, further containing Si, Mn, and Cr, with the balance being Fe and impurities. The rail shape was 136 pounds (mass: 67 kg / m). The Vickers hardness of the head surface portion 10A was 400 to 550 HV. In the metal structure of the head surface portion 10A, the pearlite area ratio was 95% or more.

[0038] [Heat treatment method in the manufacturing process of rail 1] In the manufacturing process of the rail 1 described above, a preform having a rail shape (hereinafter also referred to as a rail preform) was manufactured by hot rolling. The rail preform was then subjected to heat treatment (accelerated cooling) under the following conditions to manufacture the rail 1 having the above-mentioned characteristics. Specifically, the rail preform after hot rolling was subjected to accelerated cooling under the following conditions. The portion of the rail preform corresponding to the head surface portion 10A was cooled by accelerated cooling. The cooling start temperature was 750 to 900°C, and the cooling rate was 2.0 to 30.0°C / sec. The cooling end temperature was 500 to 660°C.

[0039] [Rolling fatigue test conditions] The rolling fatigue test conditions were as follows: In the rolling fatigue test, a rolling fatigue tester shown in FIG. 3 was used. A rail 1 with a rail shape of 136 pounds and a length of 2 m was prepared as a test specimen. A wheel 2 of AAR type with a diameter of 920 mm was also prepared. The radial load during the test was 300 kN, and the thrust load was 100 kN. The lubrication method during the test was repeated water supply and drying. Specifically, water was supplied to the rail 1 for a certain period of time during the test, and then the water supply was stopped and the rail was dried for a certain period of time (water supply and drying). During the test, the number of repeated load applications using the wheel 2 was up to 5 million times, and the cumulative passing tonnage was up to 150 million tons.

[0040] [Method of evaluating large and coarse cracks] The evaluation method for large and coarse cracks immediately below the contact surface of the rail 1 with the railway wheel after the rolling fatigue test was as follows. The evaluation area was a 300 mm long area in the longitudinal direction of the rail 1 on the surface of the head corner 12 of the rail 1. A cross section parallel to the longitudinal direction of the rail 1 after the test was used as the observation surface, and a sample including the evaluation area on the observation surface was taken. The observation surface was polished. On the observation surface after polishing, large and coarse cracks were identified immediately below the contact surface between the head corner 12 and the railway wheel. Specifically, on the observation surface, cracks with a length D (see Figures 2A to 2C) of 500 μm or more in the depth direction of the crack propagating from the surface of the head corner 12 were recognized as cracks and were evaluated. Here, the depth direction of the crack was the normal direction to the surface of the head corner 12.

[0041] [Elemental analysis around the crack to be evaluated] Elemental analysis of the area around the crack that was identified as the evaluation target was performed using the following method. The analysis area was a rectangular area including the crack, measuring 1000 μm in the longitudinal direction of the rail 1 and 1000 μm in the depth direction of the surface (contact surface) 10S. Area analysis was performed on the analysis area using an electron probe micro analyzer (EPMA), and element distribution maps of various elements were created. In the EPMA, the accelerating voltage was 15 kV, the probe current was 0.1 μA, the time was 50 ms, and the beam diameter was 2 μm.

[0042] The relationship between the obtained element distribution map and the crack morphology was examined. As a result, as shown in Figures 4A to 4C, the initial crack CRA1, which is a linear crack, was initiated in the Si-positive segregation zone SE+. On the other hand, as shown in Figure 4B, the wave-shaped propagating crack CRA2, which propagated from the initial crack CRA1 in the depth direction from the surface 10S, was initiated not in the Si-positive segregation zone SE+ but in the Si-negative segregation zone SE-.

[0043] Generally, a Si segregation band can be formed as a central segregation in the center of a cross section perpendicular to the longitudinal direction of the bloom (hereinafter referred to as the cross-sectional center) during casting of the bloom that is the raw material for the rail. Such a Si segregation band formed in the cross-sectional center of a steel material exists in the web portion 14 when the steel material is manufactured into a rail 1. This Si segregation band is referred to as a Si macro-segregation band. Therefore, it seems that a Si segregation band cannot normally exist in the head surface portion 10A, which is a part of the railhead portion 10 that is not the web portion 14.

[0044] However, as described above, the present inventors have found for the first time that the Si segregation zone (Si positive segregation zone SE+ and Si negative segregation zone SE-) also exists in the head surface portion 10A. The Si segregation zone existing in the head surface portion 10A means that a further Si segregation zone may occur around the Si macro segregation zone existing in the column portion 14. In this specification, the Si segregation zone formed around such a Si macro segregation zone is referred to as a Si semi-macro segregation zone. As described above, the Si semi-macro segregation zone may include not only the Si semi-macro positive segregation zone but also the Si semi-macro negative segregation zone.

[0045] Based on the above investigation results, the inventors have obtained the following findings. The linear initial crack CRA1 is likely to occur in the Si semi-macro positive segregation zone SE+. On the other hand, the wavy propagating crack CRA2 is likely to occur in the Si semi-macro negative segregation zone SE-. As described above, the microstructure of the head surface portion 10A of the rail 1 is substantially composed of pearlite, and the generation of hard structures such as island martensite (MA) due to the high Si content was not confirmed. Therefore, it was found that the initial crack CRA1 and the propagating crack CRA2 are caused by the Si segregation zones (Si semi-macro positive segregation zone and Si semi-macro negative segregation zone) whose existence was not known in the head surface portion 10A before.

[0046] Based on the above findings, the present inventors further investigated the relationship between the type of crack (initial crack CRA1 and propagating crack CRA2) and the Si semi-macro positive segregation degree or the Si semi-macro negative segregation degree in the region where each crack occurred. Here, the Si positive segregation degree is the ratio of the Si concentration (mass%) in the Si positive segregation zone (Si semi-macro positive segregation zone) present in the head surface portion 10A to the Si concentration (mass%) in the bulk region. Also, the Si negative segregation degree is the ratio of the Si concentration (mass%) in the Si negative segregation zone (Si semi-macro negative segregation zone) present in the head surface portion 10A to the Si concentration (mass%) in the bulk region. The method of measuring the Si positive segregation degree and the Si negative segregation degree will be described later.

[0047] As a result of the investigation, the inventors have found for the first time that in the head surface portion 10A of the rail 1 having the above-mentioned chemical composition and metal structure, if the Si positive segregation degree is more than 1.00 and less than 1.35, the occurrence of a linear initial crack CRA1 is sufficiently suppressed, and further, if the Si negative segregation degree is 0.90 to less than 1.00, the occurrence of a wavy propagating crack CRA2 is sufficiently suppressed.

[0048] The rail of this embodiment has been completed based on the above technical concept, and its gist is as follows.

[0049] The rail of the first configuration has, in mass %, C: 0.80-1.20%, Si: 0.80-2.50%, Mn: 0.10-2.00%, P: 0.0250% or less, S: 0.0250% or less, Al: 0-1.0000%, N: 0-0.0200%, Cr: 0-1.00%, Mo: 0-0.50%, Co: 0-1.00%, B: 0~0.0050%, Cu:0~1.00%, Ni:0~1.00%, V:0~0.200%, Nb:0~0.0500%, Ti:0~0.0500%, Mg:0~0.0200%, Ca:0~0.0200%, rare earth elements:0~0.0500%, Zr:0~0.0200%, and the balance is Fe and impurities. In the metal structure of the head surface portion from the head outer surface to a depth of 20 mm, the pearlite area ratio is 95% or more, and the Vickers hardness is 400HV or more. In the head surface portion, the Si positive segregation degree, which is the ratio of the maximum Si concentration in the Si positive segregation zone to the Si concentration in the bulk region, is more than 1.00 to 1.35. The degree of negative Si segregation, which is the ratio of the minimum value of the Si concentration in the negative Si segregation zone to the Si concentration in the bulk region, is 0.90 to less than 1.00.

[0050] The rail of the second configuration is the rail of the first configuration, and further comprises: Al: 0.0001 to 1.0000%, N: 0.0001 to 0.0200%, Cr: 0.01 to 1.00%, Mo: 0.01 to 0.50%, Co: 0.01 to 1.00%, B: 0.0001 to 0.0050%, Cu: 0.01 to 1.00%, Ni: 0.01 to 1.00%, V: It contains one or more selected from the group consisting of: Nb: 0.001-0.200%, Nb: 0.0001-0.0500%, Ti: 0.0001-0.0500%, Mg: 0.0001-0.0200%, Ca: 0.0001-0.0200%, rare earth elements: 0.0001-0.0500%, and Zr: 0.0001-0.0200%.

[0051] The rail of this embodiment will be described in detail below. In the following description, the unit of element content "mass %" will be simply written as "%".

[0052] [Features of the rail 1 of this embodiment] The rail of this embodiment has the following features. (Feature 1) The chemical composition, in mass%, is C: 0.80-1.20%, Si: 0.80-2.50%, Mn: 0.10-2.00%, P: 0.0250% or less, S: 0.0250% or less, Al: 0-1.0000%, N: 0-0.0200%, Cr: 0-1.00%, Mo: 0-0.50%, Co: 0-1.00%, B: 0-0 0.0050%, Cu: 0-1.00%, Ni: 0-1.00%, V: 0-0.200%, Nb: 0-0.0500%, Ti: 0-0.0500%, Mg: 0-0.0200%, Ca: 0-0.0200%, rare earth elements: 0-0.0500%, Zr: 0-0.0200%, and the balance is Fe and impurities. (Feature 2) In the metal structure of head surface portion 10A extending from head outer surface 10S to a depth of 20 mm, the pearlite area ratio is 95% or more and the Vickers hardness is 400 HV or more. (Feature 3) In the head surface portion 10A, the positive Si segregation degree, which is the ratio of the maximum Si concentration in the positive Si segregation zone to the Si concentration in the bulk region, is greater than 1.00 and 1.35. (Feature 4) In the head surface portion 10A, the negative Si segregation ratio, which is the ratio of the minimum Si concentration in the negative Si segregation zone to the Si concentration in the bulk region, is 0.90 to less than 1.00. Each feature will be explained below.

[0053] [Feature 1: Chemical composition] The chemical composition of the rail 1 according to the present embodiment contains the following elements:

[0054] C: 0.80-1.20% Carbon (C) promotes pearlite transformation and improves the wear resistance of the rail 1. If the C content is less than 0.80%, pro-eutectoid ferrite is formed, and therefore sufficient strength and wear resistance cannot be obtained. On the other hand, if the C content exceeds 1.20%, pro-eutectoid cementite is excessively formed in the head surface portion 10A, and the breakage resistance of the rail 1 decreases. Therefore, the C content is 0.80 to 1.20%. The lower limit of the C content is preferably 0.85%, more preferably 0.90%, and further preferably 0.95%. The upper limit of the C content is preferably 1.18%, more preferably 1.15%, and further preferably 1.10%. In addition, in order to stabilize the formation of pearlite structures, the C content is preferably 0.95 to 1.10%.

[0055] Silicon: 0.80 to 2.50% Silicon (Si) dissolves in ferrite in the pearlite structure and increases the hardness of the rail 1. As a result, the wear resistance of the head surface portion 10A of the rail 1 is improved. If the Si content is less than 0.80%, the above effect cannot be sufficiently obtained. On the other hand, if the Si content exceeds 2.50%, the hardenability of the steel constituting the rail 1 becomes excessively high. In this case, an excessive amount of martensite is formed in the head surface portion 10A. As a result, the wear resistance and breakage resistance of the head surface portion 10A decrease. If the Si content exceeds 2.50%, the fluctuation in the Si concentration in the steel increases further. As a result, the degree of Si segregation varies. In this case, initial cracks and / or propagating cracks become more likely to occur. As a result, large and coarse cracks become more likely to occur in the head surface portion 10A. The large and coarse cracks decrease the damage resistance of the rail 1. Therefore, the Si content is 0.80 to 2.50%. The lower limit of the Si content is preferably 0.85%, more preferably 0.90%, more preferably 0.95%, more preferably 1.00%, more preferably 1.02%, more preferably 1.05%, and more preferably 1.10%. The upper limit of the Si content is preferably 2.30%, more preferably 2.20%, and further preferably 2.00%. In addition, in order to stabilize the formation of pearlite structures and improve the wear resistance and breakage resistance of the head surface portion 10A, the Si content is preferably 1.05 to 2.20%.

[0056] Mn: 0.10-2.00% Manganese (Mn) improves the hardenability of the steel constituting the rail 1 and stabilizes the pearlite transformation. Mn also refines the lamellar spacing of pearlite, thereby increasing the hardness and wear resistance of the rail 1. If the Mn content is less than 0.10%, the effect is not sufficiently obtained. On the other hand, if the Mn content exceeds 2.00%, the hardenability of the steel constituting the rail 1 becomes excessively high. As a result, bainite and / or martensite, etc. are formed on the head surface portion 10A of the rail 1. As a result, the wear resistance and breakage resistance of the head surface portion 10A of the rail 1 decrease. An excessive amount of Mn further promotes the formation of pro-eutectoid cementite. As a result, the breakage resistance of the head surface portion 10A of the rail 1 decreases. Therefore, the Mn content is 0.10 to 2.00%. The lower limit of the Mn content is preferably 0.20%, more preferably 0.30%, and further preferably 0.40%. The upper limit of the Mn content is preferably 1.80%, more preferably 1.60%, and further preferably 1.50%. In order to stabilize the formation of pearlite structures and improve the wear resistance and breakage resistance of the rail head portion, the Mn content is preferably 0.30 to 1.60%.

[0057] P:0.0250% or less Phosphorus (P) is an impurity. In other words, the lower limit of the P content is more than 0%. If the P content exceeds 0.0250%, pearlite becomes embrittled and the breakage resistance of the rail 1 decreases. Therefore, the P content is 0.0250% or less. It is preferable that the P content is as low as possible. However, an extreme reduction in the P content significantly increases the manufacturing cost. Therefore, in consideration of industrial production, the preferable lower limit of the P content is 0.0001%, more preferably 0.0010%, more preferably 0.0020%, more preferably 0.0025%, more preferably 0.0030%, and more preferably 0.0050%. The upper limit of the P content is preferably 0.0200%, more preferably 0.0150%, and further preferably 0.0120%.

[0058] S: 0.0250% or less Sulfur (S) is an impurity. In other words, the lower limit of the S content is more than 0%. If the S content exceeds 0.0250%, coarse Mn sulfides are formed. Stress concentration is likely to occur around the coarse Mn sulfides. As a result, the breakage resistance of the rail 1 decreases. Therefore, the S content is 0.0250% or less. The S content is preferably as low as possible. However, an extreme reduction in the S content significantly increases the manufacturing cost. Therefore, in consideration of industrial production, the preferred lower limit of the S content is 0.0001%, more preferably 0.0010%, more preferably 0.0020%, more preferably 0.0030%, and even more preferably 0.0050%. The upper limit of the S content is preferably 0.0200%, more preferably 0.0150%, and further preferably 0.0120%.

[0059] [Optional Elements] The chemical composition of the rail of this embodiment may further contain, in place of a portion of Fe, one or more elements selected from the group consisting of Al: 0-1.0000%, N: 0-0.0200%, Cr: 0-1.00%, Mo: 0-0.50%, Co: 0-1.00%, B: 0-0.0050%, Cu: 0-1.00%, Ni: 0-1.00%, V: 0-0.200%, Nb: 0-0.0500%, Ti: 0-0.0500%, Mg: 0-0.0200%, Ca: 0-0.0200%, rare earth elements: 0-0.0500%, and Zr: 0-0.0200%. All of these elements are optional elements. Each optional element will be described below.

[0060] Al: 0 to 1.0000% Aluminum (Al) is an optional element and may not be contained, that is, the Al content may be 0%. When Al is contained, that is, when the Al content is more than 0%, Al deoxidizes the steel. Furthermore, Al increases the eutectoid carbon amount and the eutectoid transformation temperature. Therefore, Al suppresses the formation of pro-eutectoid cementite, which reduces toughness, and increases the hardness of the pearlite structure. As a result, the breakage resistance of the head surface portion 10A of the rail 1 is improved. The above effects can be obtained to a certain extent even if even a small amount of Al is contained. However, if the Al content exceeds 1.0000%, it becomes difficult to dissolve Al in steel. This results in the formation of coarse alumina-based inclusions. The coarse Al-based inclusions become the starting points for fatigue cracks. This reduces the damage resistance of the head surface portion 10A of the rail 1. If the Al content exceeds 1.0000%, oxides are also formed during welding of the rail 1. In this case, the weldability of the rail 1 is reduced. Therefore, the Al content is 0 to 1.0000%. The lower limit of the Al content is preferably 0.0001%, more preferably 0.0010%, and further preferably 0.0020%. The upper limit of the Al content is preferably 0.5000%, more preferably 0.1000%, further preferably 0.0800%, and further preferably 0.0500%.

[0061] N: 0~0.0200% Nitrogen (N) is an optional element and may not be contained, that is, the N content may be 0%. When N is contained, that is, when the N content is more than 0%, N segregates at the austenite grain boundaries, thereby promoting pearlite transformation from the austenite grain boundaries. This refines the pearlite block size. As a result, the toughness of the head surface portion 10A of the rail 1 is increased. When V is contained, N promotes the precipitation of V carbonitrides during the cooling process after welding of the rail 1. As a result, the hardness of pearlite is increased, and the damage resistance of the head surface portion 10A of the rail 1 is improved. Even if even a small amount of N is contained, the above effects can be obtained to a certain extent. However, if the N content exceeds 0.0200%, it becomes difficult to dissolve N in the steel, and as a result, bubbles that become the starting point of fatigue damage are more likely to form. Therefore, the N content is 0 to 0.0200%. Excessive reduction in N increases the smelting cost in the steelmaking process, so in consideration of industrial production, the lower limit of the N content is preferably 0.0001%, more preferably 0.0010%, more preferably 0.0020%, and even more preferably 0.0030%. The upper limit of the N content is preferably 0.0180%, more preferably 0.0150%, and further preferably 0.0120%.

[0062] Cr: 0~1.00% Chromium (Cr) is an optional element and may not be contained, that is, the Cr content may be 0%. When contained, that is, when the Cr content is more than 0%, Cr increases the equilibrium transformation temperature and the degree of supercooling. This refines the lamellar spacing of pearlite and increases the hardness of pearlite. As a result, the wear resistance of the head surface portion 10A of the rail 1 is improved. Even if even a small amount of Cr is contained, the above effect can be obtained to a certain extent. However, if the Cr content exceeds 1.00%, the hardenability of the steel constituting the rail 1 becomes excessively high. In this case, bainite and / or martensite, etc. are formed on the head surface portion 10A of the rail 1. As a result, the wear resistance and breakage resistance of the rail 1 decrease. If the Cr content exceeds 1.00%, Cr concentration in the segregation portion is further promoted. Therefore, the formation of martensite and pro-eutectoid cementite on the head surface portion 10A of the rail 1 is promoted. This increases the amount of martensite and / or pro-eutectoid cementite on the head surface portion 10A of the rail 1. As a result, the breakage resistance of the head surface portion 10A of the rail 1 decreases. Therefore, the Cr content is 0 to 1.00%. The lower limit of the Cr content is preferably 0.01%, more preferably 0.02%, more preferably 0.03%, more preferably 0.04%, more preferably 0.06%, more preferably 0.08%, and more preferably 0.10%. The upper limit of the Cr content is preferably 0.95%, more preferably 0.90%, and further preferably 0.80%.

[0063] Mo: 0 to 0.50% Molybdenum (Mo) is an optional element and may not be contained, that is, the Mo content may be 0%. When Mo is contained, that is, when the Mo content is more than 0%, Mo increases the equilibrium transformation temperature and the degree of supercooling. This refines the lamellar spacing of pearlite and increases the hardness of pearlite. As a result, the wear resistance of the head surface portion 10A of the rail 1 is improved. Even if even a small amount of Mo is contained, the above effects can be obtained to a certain extent. However, if the Mo content exceeds 0.50%, the transformation rate significantly decreases, and martensite is formed in the head surface portion 10A of the rail 1. As a result, the breakage resistance of the head surface portion 10A of the rail 1 decreases. Therefore, the Mo content is 0 to 0.50%. The lower limit of the Mo content is preferably 0.01%, more preferably 0.02%, further preferably 0.05%, and further preferably 0.10%. The upper limit of the Mo content is preferably 0.45%, more preferably 0.40%, and further preferably 0.30%.

[0064] Co: 0 to 1.00% Cobalt (Co) is an optional element and may not be contained, that is, the Co content may be 0%. When Co is contained, that is, when the Co content is more than 0%, Co dissolves in ferrite in pearlite and refines the lamellar structure of pearlite in the surface layer including the head outer surface (rolling surface) 10S of the rail 1. This increases the hardness of the head outer surface 10S and improves the wear resistance of the head surface portion 10A of the rail 1. Even if even a small amount of Co is contained, the above effect can be obtained to a certain extent. However, if the Co content exceeds 1.00%, the lamellar structure cannot be sufficiently refined in accordance with the Co content, and further, the production cost increases. Therefore, the Co content is 0 to 1.00%. The lower limit of the Co content is preferably 0.01%, more preferably 0.02%, further preferably 0.05%, and further preferably 0.10%. The upper limit of the Co content is preferably 0.90%, more preferably 0.80%, and further preferably 0.60%.

[0065] B: 0 to 0.0050% Boron (B) is an optional element and may not be contained, that is, the B content may be 0%. When B is present, that is, when the B content is more than 0%, B forms iron boride (Fe 23 (CB)6) is formed to promote pearlite transformation. This reduces the cooling rate dependency of the pearlite transformation temperature. This reduces the hardness gradient inside the head surface portion 10A of the rail 1. As a result, the generation of crack damage in the head surface portion 10A of the rail 1 due to contact with the wheel is suppressed. If even a small amount of B is contained, the above effects can be obtained to a certain extent. However, if the B content exceeds 0.0050%, coarse iron boride particles are formed, which promotes brittle fracture and reduces the breakage resistance of the head surface portion 10A of the rail 1. Therefore, the B content is 0 to 0.0050%. The lower limit of the B content is preferably 0.0001%, more preferably 0.0002%, still more preferably 0.0005%, and still more preferably 0.0010%. The upper limit of the B content is preferably 0.0040%, more preferably 0.0030%, and further preferably 0.0020%.

[0066] Cu: 0-1.00% Copper (Cu) is an optional element and may not be contained, that is, the Cu content may be 0%. When contained, that is, when the Cu content is more than 0%, Cu dissolves in ferrite in pearlite and increases the hardness of the head surface portion 10A of the rail 1 through solid solution strengthening. As a result, the wear resistance of the head surface portion 10A of the rail 1 is improved. Even if even a small amount of Cu is contained, the above effect can be obtained to a certain extent. However, if the Cu content exceeds 1.00%, the hardenability of the steel constituting the rail 1 becomes excessively high, which causes martensite to form in the head surface portion 10A of the rail 1. As a result, the breakage resistance of the head surface portion 10A of the rail 1 decreases. Therefore, the Cu content is 0 to 1.00%. The lower limit of the Cu content is preferably 0.01%, more preferably 0.02%, further preferably 0.05%, and further preferably 0.10%. The upper limit of the Cu content is preferably 0.90%, more preferably 0.80%, and even more preferably 0.70%. In order to sufficiently increase the hardness of the rail head and suppress the formation of martensite, the upper limit of the Cu content is more preferably 0.40%.

[0067] Ni: 0 to 1.00% Nickel (Ni) is an optional element and may not be contained, that is, the Ni content may be 0%. When contained, that is, when the Ni content is more than 0%, Ni increases the toughness of pearlite. Ni also increases the hardness of the head surface portion 10A of the rail 1 by solid solution strengthening. As a result, the wear resistance of the head surface portion 10A of the rail 1 is improved. The above effects can be obtained to some extent if even a small amount of Ni is contained. However, if the Ni content exceeds 1.00%, the hardenability of the steel constituting the rail 1 becomes excessively high, which causes martensite to form in the head surface portion 10A of the rail 1. As a result, the wear resistance and breakage resistance of the head surface portion 10A of the rail 1 decrease. Therefore, the Ni content is 0 to 1.00%. The lower limit of the Ni content is preferably 0.01%, more preferably 0.02%, further preferably 0.05%, and further preferably 0.10%. The upper limit of the Ni content is preferably 0.90%, more preferably 0.80%, and further preferably 0.70%.

[0068] V: 0~0.200% Vanadium (V) is an optional element and may not be contained, that is, the V content may be 0%. When V is contained, that is, when the V content is more than 0%, V forms V precipitates such as V carbides, V nitrides, and V carbonitrides during the cooling process after hot rolling in the manufacturing process of the rail 1. Precipitation hardening by these V precipitates increases the hardness of pearlite. As a result, the damage resistance of the head surface portion 10A of the rail 1 is improved. Even if even a small amount of V is contained, the above effect can be obtained to a certain extent. However, if the V content exceeds 0.200%, fine V precipitates are formed in an excessive amount, which embrittles pearlite, resulting in a decrease in the damage resistance of the head surface portion 10A of the rail 1. Therefore, the V content is 0 to 0.200%. The lower limit of the V content is preferably 0.001%, more preferably 0.005%, more preferably 0.010%, more preferably 0.020%, more preferably 0.030%, and more preferably 0.050%. The upper limit of the V content is preferably 0.180%, more preferably 0.150%, more preferably 0.120%, more preferably 0.100%, and even more preferably 0.080%.

[0069] Nb: 0 to 0.0500% Niobium (Nb) is an optional element and may not be contained, that is, the Nb content may be 0%. When Nb is contained, that is, when the Nb content is more than 0%, Nb forms Nb precipitates such as Nb carbides and Nb nitrides during the cooling process after hot rolling in the manufacturing process of the rail 1. The precipitation hardening caused by these Nb precipitates increases the hardness of pearlite. As a result, the damage resistance of the head surface portion 10A of the rail 1 is improved. Nb is further c1 Nb precipitates are formed in the heat-affected zone (HAZ) of a weld that is reheated to a temperature range below the 1000°C point. This suppresses the softening of the heat-affected zone (HAZ) of a welded joint. Even if only a small amount of Nb is contained, the above effect can be obtained to some extent. However, if the Nb content exceeds 0.0500%, excessive Nb precipitates are formed, which embrittles pearlite and reduces the damage resistance of the head surface portion 10A of the rail 1. Therefore, the Nb content is 0 to 0.0500%. The lower limit of the Nb content is preferably 0.0001%, more preferably 0.0010%, more preferably 0.0020%, more preferably 0.0025%, and even more preferably 0.0030%. The upper limit of the Nb content is preferably 0.0400%, more preferably 0.0300%, and further preferably 0.0200%.

[0070] Ti: 0 to 0.0500% Titanium (Ti) is an optional element and may not be contained, that is, the Ti content may be 0%. When Ti is contained, that is, when the Ti content is more than 0%, Ti forms Ti precipitates such as Ti carbides and Ti nitrides during the cooling process after hot rolling in the manufacturing process of the rail 1. The precipitation hardening caused by these Ti precipitates increases the hardness of pearlite. As a result, the damage resistance of the head surface portion 10A of the rail 1 is improved. Furthermore, the Ti precipitates are difficult to dissolve in the parent phase during reheating during welding. Therefore, the Ti precipitates refine the structure of the heat-affected zone (HAZ) that is heated to the austenite temperature range. As a result, embrittlement of the welded joint is suppressed. The above effect can be obtained to some extent if even a small amount of Ti is contained. However, if the Ti content exceeds 0.0500%, coarse Ti precipitates are formed. In this case, fatigue cracks are likely to be generated due to stress concentration around the coarse Ti precipitates. As a result, the damage resistance of the head surface portion 10A of the rail 1 is reduced. Therefore, the Ti content is 0 to 0.0500%. The lower limit of the Ti content is preferably 0.0001%, more preferably 0.0010%, more preferably 0.0020%, more preferably 0.0030%, more preferably 0.0035%, and more preferably 0.0040%. The upper limit of the Ti content is preferably 0.0450%, more preferably 0.0400%, further preferably 0.0300%, and further preferably 0.0200%.

[0071] Magnesium: 0 to 0.0200% Magnesium (Mg) is an optional element and may not be contained, that is, the Mg content may be 0%. When Mg is contained, that is, when the Mg content is more than 0%, Mg combines with S to form fine sulfides (MgS). This MgS finely disperses MnS. Therefore, stress concentration around the MnS is alleviated. As a result, the damage resistance of the head surface portion 10A of the rail 1 is improved. Even if even a small amount of Mg is contained, the above effect can be obtained to some extent. However, if the Mg content exceeds 0.0200%, coarse Mg oxides are generated. In this case, stress concentration around the coarse Mg oxides makes fatigue cracks more likely to occur. As a result, the damage resistance of the head surface portion 10A of the rail 1 decreases. Therefore, the Mg content is 0 to 0.0200%. The lower limit of the Mg content is preferably 0.0001%, more preferably 0.0005%, more preferably 0.0010%, more preferably 0.0015%, and more preferably 0.0030%. The upper limit of the Mg content is preferably 0.0180%, more preferably 0.0150%, and further preferably 0.0120%.

[0072] Ca: 0 to 0.0200% Calcium (Ca) is an optional element and may not be contained, that is, the Ca content may be 0%. When contained, that is, when the Ca content is more than 0%, Ca combines with S to form sulfide (CaS). This CaS finely disperses MnS. Therefore, stress concentration around MnS is alleviated. As a result, the damage resistance of the head surface portion 10A of the rail 1 is improved. Even if even a small amount of Ca is contained, the above effect can be obtained to some extent. However, if the Ca content exceeds 0.0200%, coarse Ca oxides are formed. In this case, stress concentration around the coarse Ca oxides makes fatigue cracks more likely to occur. As a result, the damage resistance of the head surface portion 10A of the rail 1 decreases. Therefore, the Ca content is 0 to 0.0200%. The lower limit of the Ca content is preferably 0.0001%, more preferably 0.0005%, more preferably 0.0010%, more preferably 0.0020%, and even more preferably 0.0030%. The upper limit of the Ca content is preferably 0.0180%, more preferably 0.0150%, and further preferably 0.0120%.

[0073] Rare earth elements (REM): 0~0.0500% Rare earth elements (REM) are optional elements and may not be included, i.e., the REM content may be 0%. When REM is contained, that is, when the REM content is more than 0%, REM generates oxysulfides (REM2O2S) and becomes the nuclei for the formation of Mn sulfide-based inclusions. Oxysulfides have a high melting point. Therefore, they suppress the elongation of Mn sulfide-based inclusions after hot rolling. As a result, REM finely disperses MnS and relieves stress concentration around MnS. As a result, the damage resistance of the head surface portion 10A of the rail 1 is improved. The above effect can be obtained to some extent even if even a small amount of REM is contained. However, if the REM content exceeds 0.0500%, coarse REM oxysulfides are generated, and in this case, fatigue cracks are likely to be generated due to stress concentration around the coarse REM oxysulfides, resulting in a decrease in the damage resistance of the head surface portion 10A of the rail 1. Therefore, the REM content is 0 to 0.0500%. The lower limit of the REM content is preferably 0.0001%, more preferably 0.0005%, more preferably 0.0010%, more preferably 0.0020%, and even more preferably 0.0030%. The upper limit of the REM content is preferably 0.0400%, more preferably 0.0300%, and even more preferably 0.0250%.

[0074] In this specification, REM refers to one or more elements selected from the group consisting of scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and the lanthanides lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71. In addition, in this specification, the REM content refers to the total content of these elements.

[0075] Zr: 0 to 0.0200% Zirconium (Zr) is an optional element and may not be contained, that is, the Zr content may be 0%. When Zr is contained, that is, when the Zr content is more than 0%, Zr generates ZrO2 inclusions. ZrO2 has high lattice matching with austenite (γ-Fe). Therefore, it becomes the solidification nucleus of the steel constituting the rail 1, in which γ-Fe is the solidification primary crystal, and increases the equiaxed crystallization rate of the solidification structure. This suppresses the formation of a segregation zone in the center of the cast slab. This suppresses the formation of martensite in the head surface portion 10A of the rail 1. As a result, the breakage resistance of the head surface portion 10A of the rail 1 is improved. Even if even a small amount of Zr is contained, the above effects can be obtained to a certain extent. However, if the Zr content exceeds 0.0200%, coarse Zr-based inclusions are formed in an excessive amount, and fatigue cracks are easily generated due to stress concentration around the coarse Zr-based inclusions, resulting in a decrease in the damage resistance of the head surface portion 10A of the rail 1. Therefore, the Zr content is 0 to 0.0200%, and if contained, it is 0.0200% or less. The lower limit of the Zr content is preferably 0.0001%, more preferably 0.0010%, further preferably 0.0020%, and further preferably 0.0030%. The upper limit of the Zr content is preferably 0.0180%, more preferably 0.0150%, and further preferably 0.0120%.

[0076] The balance of the chemical composition of the rail 1 of this embodiment is composed of Fe and impurities. Here, the impurities in the chemical composition refer to those that are mixed in from raw materials such as ore, scrap, or the manufacturing environment during industrial production of the rail 1, and are acceptable within a range that does not adversely affect the rail 1 of this embodiment. The chemical composition of the rail 1 of this embodiment may contain, as an impurity other than the above-mentioned impurities, for example, O: 0.0060% or less. The O content may be 0.0001% or more, 0.0010% or more, or 0.0020% or more.

[0077] [(Feature 2) Metal structure and hardness of head surface 10A] In the rail 1 of this embodiment, in the metal structure of the head surface portion 10A, the area ratio of pearlite is 95% or more and the Vickers hardness is 400 HV or more.

[0078] [Metal structure of head surface 10A] In the metal structure of steel materials with the same hardness, pearlite has the highest wear resistance. In other words, pearlite has better wear resistance than ferrite, cementite, bainite, and martensite. Therefore, the metal structure of the head surface portion 10A of this embodiment is substantially pearlite. Specifically, the area ratio of pearlite in the metal structure of the head surface portion 10A is 95% or more.

[0079] The remaining structure other than pearlite in the metal structure of the head surface portion 10A is one or more selected from the group consisting of ferrite, cementite, bainite, and martensite. If the pearlite area ratio is 95% or more and the area ratio of the remaining structure is 5% or less, the remaining structure other than pearlite has almost no effect on the wear resistance and damage resistance of the head surface portion 10A. The pearlite area ratio is preferably 98% or more, and most preferably 100%.

[0080] The metal structure of the portion other than the head surface portion 10A of the rail 1 is not particularly limited. The metal structure of the portion other than the head surface portion 10A may be a structure consisting of ferrite and pearlite, or may be a ferrite structure or a bainite structure. Considering the continuity from the metal structure of the head surface portion 10A, the preferred metal structure of the portion other than the head surface portion 10A is a structure consisting of ferrite and pearlite.

[0081] [Vickers hardness of head surface 10A] The Vickers hardness of the head surface portion 10A is 400HV or more. If the Vickers hardness of the head surface portion 10A is less than 400HV, sufficient wear resistance and damage resistance cannot be obtained in the head surface portion 10A of the rail 1. Therefore, the Vickers hardness of the head surface portion 10A is 400HV or more.

[0082] The lower limit of the Vickers hardness of the head surface portion 10A is preferably 420 HV, and more preferably 450 HV. The upper limit of the Vickers hardness of the head surface portion 10A is not particularly limited, but is, for example, 650HV, preferably 600HV, and more preferably 550HV.

[0083] [Method of observing the metal structure of the head surface portion 10A] The pearlite area ratio of the head surface portion 10A is determined by the following method. A sample is taken from the head surface portion 10A, including a position 10 mm deep from the surface of the head surface portion 10A, in a cross section perpendicular to the longitudinal direction of the rail 1. Of the surface of the taken sample, a cross section perpendicular to the longitudinal direction of the rail 1 is defined as the observation surface. The observation surface of the sample is mirror-polished. The mirror-polished observation surface is etched using 3% nitric acid alcohol (Nital etching solution). Of the etched observation surface, a position 10 mm deep from the surface of the head surface portion 10A is observed using an optical microscope at a magnification of 200 times. A photograph is taken, and the observation field of view (400 μm x 300 μm) is designated as the evaluation area.

[0084] In the observation field, pearlite can be easily distinguished from other structures (proeutectoid ferrite, proeutectoid cementite, bainite, martensite, etc.) by contrast. Ferrite is observed as a white area. Pearlite is observed as a black and white layer or a dark gray color. Bainite and martensite are observed as areas brighter than the gray color of pearlite. Proeutectoid cementite, like ferrite, is observed as a white area. Pearlite is identified based on the above-mentioned contrast. Then, the area ratio of pearlite is calculated based on the total area of ​​the identified pearlite and the total area of ​​the observation field. The area ratio of pearlite may be calculated using image analysis software or the like.

[0085] The above-mentioned samples are taken from 10 arbitrary positions on the head surface portion 10A of the rail 1, and the pearlite area ratio is determined for each sample. The arithmetic mean value of the pearlite area ratios at the 10 positions is defined as the pearlite area ratio (%) of the head surface portion 10A of the rail 1.

[0086] [Method of measuring Vickers hardness of head surface 10A] The Vickers hardness of the head surface portion 10A is determined by the following method. Specifically, a test piece having a cross section perpendicular to the longitudinal direction of the rail 1 as a measurement surface is taken from the rail 1. Referring to Fig. 5, a line segment extending in the depth direction from the width center position P11 of the head top part 11 on the head outer surface 10S on the measurement surface is taken as a hardness measurement line L11. The hardness measurement line L11 is coaxial with the normal line of the head outer surface 10S at position P11. On the hardness measurement line L11, the measurement points are located at a depth of 1 mm, a depth of 10 mm, and a depth of 20 mm from position P11 in the depth direction.

[0087] In addition, the line segment L13, which is a tangent to the jaw lower part 13 on the measurement surface of the rail 1, L and L13 R Let us assume that the line segment L13 L and L13 R The intersection point is defined as position P13. Position P13 is located on the hardness measurement line L11.

[0088] At the head corner portion 12L of the measurement surface, the line segment connecting point E and point P13 is the hardness measurement line L12. L From point E to hardness measurement line L12 L The measurement points are located at depths of 1 mm, 10 mm, and 20 mm in the depth direction along the line. Similarly, at the head corner portion 12R, the line segment connecting point F and point P13 is the hardness measurement line L12. R From point F to hardness measurement line L12 R The measurement points are located at depths of 1 mm, 10 mm, and 20 mm in the depth direction along the line. At each measurement point, a Vickers hardness test in accordance with JIS Z 2241-1 (2020) is performed to obtain the Vickers hardness (HV). At this time, the test force is 10 kgf.

[0089] Three hardness measurement lines L11, L12 L , L12R The arithmetic mean value of the same depth measurement points (3 points) is taken as the hardness at that depth position. Specifically, the hardness measurement lines L11 and L12 L , L12 R The arithmetic average of the three hardness values ​​at a depth of 1 mm is defined as the Vickers hardness H1 (HV) at a depth of 1 mm. Hardness measurement lines L11 and L12 L , L12 R The arithmetic average of the three hardness values ​​at a depth of 10 mm is defined as the Vickers hardness H10 (HV) at a depth of 1 mm. Hardness measurement lines L11 and L12 L , L12 R The arithmetic average of the three hardness values ​​at a depth of 20 mm is defined as the Vickers hardness H20 (HV) at a depth of 1 mm.

[0090] If the obtained Vickers hardness H1 at a depth of 1 mm, the Vickers hardness H10 at a depth of 10 mm, and the Vickers hardness H20 at a depth of 20 mm are all 400 HV or more, the Vickers hardness of the head surface portion 10A is determined to be 400 HV or more.

[0091] [(Feature 3) Degree of positive Si segregation in the head surface area 10A] Furthermore, in the rail 1 of this embodiment, the head surface portion 10A has a degree of positive Si segregation of more than 1.00 to 1.35. If the degree of positive silicon segregation exceeds 1.35, initial cracks are likely to occur. If initial cracks occur, they are likely to grow into large cracks. As a result, the damage resistance of the rail 1 decreases. If the degree of positive Si segregation is 1.35 or less, the occurrence of initial cracks is sufficiently suppressed, and therefore the rail 1 can have excellent damage resistance. The upper limit of the degree of positive Si segregation is preferably 1.34, more preferably 1.32, more preferably 1.30, more preferably 1.28, more preferably 1.25, more preferably 1.20, and more preferably 1.15. The lower limit of the Si positive segregation degree is higher than 1.00. The lower limit of the Si positive segregation degree is preferably as close to 1.00 as possible. However, excessive reduction in the lower limit of the Si positive segregation degree increases the manufacturing cost. Therefore, in consideration of the manufacturing cost, the preferred lower limit of the Si positive segregation degree is 1.01, more preferably 1.03, and even more preferably 1.05.

[0092] [(Feature 4) Degree of negative Si segregation in the head surface area 10A] Furthermore, in the rail 1 of this embodiment, the head surface portion 10A has a negative Si segregation degree of 0.90 to less than 1.00. If the degree of negative Si segregation is less than 0.90, a propagating crack originating from an initial crack is likely to grow. The reason for this is unclear, but the following is thought to be the reason. As described above, Si dissolves and increases the strength of ferrite in pearlite. However, if the degree of negative Si segregation is less than 0.90, the strength of ferrite in pearlite decreases in the semi-macrosegregation region of negative Si segregation. As a result, the propagating crack is likely to grow. If the propagating crack grows, coarse and large cracks are generated. As a result, the damage resistance of the rail 1 decreases. If the degree of negative Si segregation is 0.90 or more, the growth of a propagating crack is sufficiently suppressed, and therefore the rail 1 can have excellent damage resistance.

[0093] The lower limit of the degree of negative Si segregation is preferably 0.91, more preferably 0.92, still more preferably 0.95, still more preferably 0.97, and still more preferably 0.99. The upper limit of the negative Si segregation is less than 1.00. The upper limit of the negative Si segregation is preferably as close to 1.00 as possible. However, an excessive increase in the lower limit of the negative Si segregation increases the manufacturing cost. Therefore, in consideration of the manufacturing cost, the upper limit of the positive Si segregation is preferably 0.99, and more preferably 0.98.

[0094] [Method of measuring the degree of Si positive segregation and the degree of Si negative segregation in the head surface portion 10A] The Si positive segregation degree and the Si negative segregation degree in the head surface portion 10A are determined by the following method. A test piece is taken with a cross section extending in the depth direction (normal direction at point P11 on the surface of the rail head 10) and the longitudinal direction of the rail 1 as the measurement surface, starting from point P11 (see FIG. 1B) at the width center of the surface of the rail head 10 of the rail 1. Five analysis areas are selected from the measurement surface of the test piece, ranging from a depth of 10 mm to a depth of 20 mm starting from the surface of the rail head 10, and each analysis area is 800 μm in the longitudinal direction of the rail 1 and 800 μm in the depth direction. At this time, the five analysis areas are arranged consecutively in the longitudinal direction of the rail 1, so that the ends of adjacent analysis areas are in contact with each other.

[0095] A surface analysis is performed on the analysis area using an electron probe micro analyzer (EPMA) to create an element distribution map of the Si concentration. In the EPMA, the accelerating voltage is 15 kV, the probe current is 0.1 μA, the time is 50 ms, and the beam diameter is 2 μm.

[0096] Based on the element distribution map, the Si semi-macro positive segregation zone and the Si semi-macro negative segregation zone are identified. Specifically, in each analysis region, the average Si concentration [Si] in the analysis region is calculated based on the element distribution map of the Si concentration obtained. The above element distribution map is divided into the following four Si concentration regions, with the average Si concentration [Si] as the median. In other words, the element map is quaternized, with the average Si concentration [Si] as the median. Area 1: Area higher than 1.15×[Si] Area 2: Area greater than or equal to [Si] and less than or equal to 1.15 × [Si] Area 3: Area greater than or equal to 0.85 × [Si] and less than [Si] Area 4: Area less than 0.85 × [Si] Of the four-valued analysis regions, the region corresponding to area 1 is recognized as a Si semi-macro positive segregation zone. Of the four-valued analysis regions, the region corresponding to area 4 is recognized as a Si semi-macro negative segregation zone. 50 locations of Si semi-macro positive segregation zones are selected from the five analysis regions. Similarly, 50 locations of Si semi-macro negative segregation zones are selected from the five analysis regions. In the selected Si semi-macro positive segregation zone and the selected Si semi-macro negative segregation zone, the Si positive segregation degree and the Si negative segregation degree are obtained by the following method.

[0097] [Method of measuring the degree of positive silicon segregation] FIG. 6 is a schematic diagram for explaining how to obtain the degree of Si positive segregation. Referring to FIG. 6, the element distribution map of the Si concentration of the EPMA described above is composed of a plurality of line analyses (line scans). Therefore, among the plurality of line analyses constituting the element distribution map of the Si concentration, a line analysis that crosses the specified Si semi-macro positive segregation zone is selected to obtain the Si concentration distribution at the line. Specifically, when the Si semi-macro positive segregation zone has a shape with a large aspect ratio such as an ellipse, a line analysis that passes through approximately the center of the Si segregation zone in the longitudinal direction is selected.

[0098] [Quantification of Si concentration in the bulk region] 6, in the Si concentration distribution obtained by the selected line analysis, the arithmetic mean value (mass%) of the Si concentration is calculated for each of the bulk regions L1 (1000 μm) and R1 (1000 μm) that exist on either side of the Si semi-macro positive segregation zone. The lower value of the average Si concentration in the bulk region L1 and the average Si concentration in the bulk region R1 is determined as the Si concentration (mass%) in the bulk region.

[0099] [Quantification of Si concentration in the Si semi-macro positive segregation zone] Furthermore, in the Si concentration analysis obtained by the selected line analysis, the maximum value of the Si concentration in the Si semi-macro positive segregation zone is obtained, and the arithmetic average value of the maximum value of the Si concentration and the Si concentration in the above-mentioned bulk region is set as the Si concentration (mass%) in the Si semi-macro positive segregation zone.

[0100] [Determination of the degree of positive silicon segregation] Based on the Si concentration in the bulk region and the Si concentration in the Si semi-macro positive segregation zone obtained by the above-mentioned method, the degree of Si segregation in the Si semi-macro positive segregation zone is calculated by the following formula. Degree of positive silicon segregation = Si concentration in the silicon semi-macro positive segregation zone / Si concentration in the bulk region The degree of Si positive segregation is obtained for each of the 50 Si semi-macro positive segregation zones by the above-mentioned method. The arithmetic average value of the top 20 obtained Si positive segregation degrees is regarded as the Si positive segregation degree in the Si semi-macro positive segregation zone.

[0101] [Method of measuring negative silicon segregation] FIG. 7 is a schematic diagram for explaining how to obtain the degree of Si negative segregation. Referring to FIG. 7, the element distribution map of the Si concentration of the EPMA described above is composed of a plurality of line analyses (line scans). Therefore, among the plurality of line analyses constituting the element distribution map of the Si concentration, a line analysis that crosses the specified Si semi-macro negative segregation zone is selected to obtain the Si concentration distribution at the line. Specifically, when the Si semi-macro negative segregation zone has a shape with a large aspect ratio such as an ellipse, a line analysis that passes through approximately the center of the Si segregation zone in the longitudinal direction is selected.

[0102] [Quantification of Si concentration in the bulk region] 7, in the Si concentration distribution obtained by the selected line analysis, the arithmetic mean value (mass%) of the Si concentration is calculated for each of the bulk regions L1 (1000 μm) and R1 (1000 μm) that exist on either side of the Si semi-macro negative segregation zone. The lower value of the average Si concentration in the bulk region L1 and the average Si concentration in the bulk region R1 is determined as the Si concentration (mass%) in the bulk region.

[0103] [Quantification of Si concentration in the Si semi-macro negative segregation zone] Furthermore, in the Si concentration analysis obtained by the selected line analysis, the maximum value of the Si concentration in the Si semi-macro negative segregation zone is obtained, and the arithmetic average value of the minimum value of the Si concentration and the Si concentration in the above-mentioned bulk region is set as the Si concentration (mass%) in the Si semi-macro negative segregation zone.

[0104] [Determination of the degree of negative Si segregation] Based on the Si concentration in the bulk region and the Si concentration in the Si semi-macro negative segregation zone obtained by the above-mentioned method, the degree of Si segregation in the Si semi-macro negative segregation zone is calculated by the following formula. Degree of negative Si segregation = Si concentration in the Si semi-macro negative segregation zone / Si concentration in the bulk region The degree of Si negative segregation is obtained for each of the 50 Si semi-macro negative segregation zones by the above-mentioned method. The arithmetic average value of the top 20 obtained Si negative segregation degrees is regarded as the Si negative segregation degree in the Si semi-macro negative segregation zone.

[0105] [Effects of the rail 1 of this embodiment] The rail 1 of this embodiment satisfies Features 1 to 4. Therefore, the rail 1 of this embodiment has excellent wear resistance and damage resistance.

[0106] [Manufacturing method of the rail 1 of this embodiment] An example of a method for manufacturing the rail 1 of this embodiment will be described below. The method for manufacturing the rail 1 described below is one example for manufacturing the rail 1 of this embodiment. Therefore, the rail 1 having the above-mentioned configuration may be manufactured by a manufacturing method other than the manufacturing method described below. However, the manufacturing method described below is a preferred example of a method for manufacturing the rail 1 of this embodiment.

[0107] An example of a method for manufacturing the rail 1 of this embodiment includes the following steps. (Process 1) Material manufacturing process (Process 2) Hot rolling process (Step 3) Heat treatment step The rail 1 of this embodiment is obtained by preparing a bloom having a chemical composition that satisfies Feature 1 (step 1), reheating the bloom and then hot rolling it to form a preform having a rail shape (step 2), and then subjecting the preform to controlled cooling (step 3). Each step will be described below.

[0108] [(Process 1) Material manufacturing process] In the material production process, a bloom is produced as the material for the rail 1 of this embodiment. Specifically, molten steel having a chemical composition that satisfies Feature 1 is produced by melting in a commonly used melting furnace such as a converter or an electric furnace. The produced molten steel is then used to produce the bloom by continuous casting.

[0109] [Continuous casting conditions to satisfy feature 3] In the continuous casting, the bloom is lightly reduced. If the bloom is lightly reduced in the continuous casting, the degree of positive silicon segregation of the bloom is reduced. If the degree of positive silicon segregation of the bloom is reduced, the degree of positive silicon segregation of the rail 1 to be produced is also reduced.

[0110] The soft reduction in continuous casting satisfies the following conditions: (Condition 1) Soft reduction begins when the central solid fraction of the bloom is 10 to 25%. (Condition 2) The soft reduction is terminated when the central solid fraction of the bloom exceeds 70%. These conditions are explained below.

[0111] [Regarding condition 1] The degree of silicon segregation correlates with the central solid fraction of the bloom when it is lightly reduced. Specifically, immediately after the bloom leaves the mold, only the surface layer is solidified and the inside is molten. As the bloom leaves the mold and moves downstream, the internal solidification of the bloom progresses and the central solid fraction increases. Here, the central solid fraction of the bloom means the solidification ratio in a 20 mm x 20 mm region (hereinafter also referred to as the center of the bloom) in a cross section (height 320 mm x width 380 mm) perpendicular to the longitudinal direction of the bloom. When the entire center of the bloom is solidified, the central solid fraction of the bloom is 100%.

[0112] If the bloom is lightly reduced when the central solid fraction of the bloom is low, that is, when the internal solidification of the bloom has not progressed, the positive Si segregation in the bloom is suppressed. In this embodiment, the soft reduction is started when the central solid fraction is 10 to 25%. If the central solid fraction of the bloom at the start of the soft reduction exceeds 25%, the reduction does not sufficiently penetrate into the inside of the bloom even if the soft reduction is performed. Therefore, the positive Si segregation degree is not sufficiently reduced. On the other hand, if the central solid fraction of the bloom at the start of the soft reduction is less than 10%, the bloom is in a state in which it has not been sufficiently solidified. Even if the bloom in such a state is lightly reduced, the positive Si segregation degree is not sufficiently reduced. Therefore, the soft reduction is started when the central solid fraction is 10 to 25%. The positive Si segregation degree can be further suppressed by starting the soft reduction when the central solid fraction is 20% or less.

[0113] [Regarding condition 2] Furthermore, the soft reduction is terminated when the central solid fraction of the bloom exceeds 70%. If the soft reduction is terminated when the central solid fraction is 70% or less, the reduction does not sufficiently penetrate to the center of the bloom. As a result, the degree of positive Si segregation may not be sufficiently reduced. If the soft reduction is terminated when the central solid fraction exceeds 70%, the reduction will sufficiently penetrate to the center of the bloom. As a result, the degree of positive Si segregation will be sufficiently reduced. When the central solid fraction of the bloom exceeds 70%, the reduction ratio of the soft reduction is set to 40 to 70% of the reduction ratio when the central solid fraction is 70% or less.

[0114] The reduction ratio in soft reduction refers to the ratio of the amount of reduction in soft reduction to the height (thickness) of the bloom before the start of soft reduction. Specifically, it can be defined by the following formula. Reduction rate under soft reduction (%) = (thickness of bloom before soft reduction starts - reduction amount under soft reduction) / thickness of bloom before soft reduction starts x 100

[0115] When the central solid fraction exceeds 70%, the total reduction ratio of the soft reduction (that is, the reduction ratio of the soft reduction in this embodiment) is 2 to 5%.

[0116] By carrying out soft reduction during continuous casting under the above conditions, the degree of positive Si segregation of the produced rail 1 is reduced to 1.35 or less.

[0117] The central solid fraction of the bloom is calculated as follows: The temperature at the center of the bloom in the thickness direction during continuous casting is calculated by one-dimensional heat transfer and solidification calculation. The enthalpy method is used for the heat transfer and solidification calculation.

[0118] Specifically, the bloom is divided into N elements in the thickness direction. N=1000. The initial temperature of all elements is the molten steel temperature (℃) at the time when it is poured from the tundish into the mold. At each time step, the solid fraction and enthalpy of each element are calculated. Here, the time step Δt is 1 second. Solid fraction FS of element i (i = 1 to N) at the nth time step n i is expressed by the following equation (A).

[0119]

number

[0120] Here, T.C. n i is the temperature of element i at the nth time step (°C). TS is the solidus temperature, TL is the liquidus temperature, and TC n i satisfies the following formula: TS≦TC n i ≦TL

[0121] Also, the enthalpy of element i at the nth time step, H n i is calculated based on the following formula (B). H n i =ρ×c×(TC n i -Tref) + ρ × L × FS n i (B) In formula (B), ρ is density, c is specific heat, Tref is reference temperature, and L is latent heat. Here, density ρ is 7800 kg / m 3 , the specific heat C is 700J / (kg·K), the reference temperature Tref=0℃, and the latent heat L is 250kJ / kg. The enthalpy H of the next time step (the n+1th time step) is calculated using the following equation (C), which is a discretized version of the heat conduction equation: n+1 i Request.

[0122]

number

[0123] Here, H n+1 i and H n i is the enthalpy of element i at the n+1th and nth time steps. TC n i+1 and T.C. n i-1 is the temperature of the adjacent element of element i. k is the thermal conductivity. Δt is the time step, and Δx is the size of element i (i.e., the bloom thickness divided by N). The thermal conductivity k at temperature T is calculated using the following equation: k=39.0-0.0138×(T-500)

[0124] The resulting enthalpy H n+1 i Using equations (A) and (B), the temperature TC of the next time step (the n+1th time step) is calculated. n i-1 Request. The change in the solid fraction at the center position of the bloom (i=N / 2) over time is tracked to determine the central solid fraction, which is the solid fraction at the center position of the bloom.

[0125] [(Process 2) Hot rolling process] The produced bloom is reheated and then hot rolled to form a rail blank.

[0126] First, the bloom is charged into a heating furnace and reheated. If the heating temperature of the bloom during reheating is less than 1000°C, sufficient formability during hot rolling cannot be ensured. In addition, rolling defects are likely to occur during hot rolling. On the other hand, if the heating temperature of the bloom during reheating exceeds 1350°C, the steel may melt and rail manufacturing may become difficult. Therefore, the heating temperature of the bloom during reheating is set to 1000 to 1350°C. After the bloom is heated to within this temperature range, it is extracted from the heating furnace. Then, the bloom is hot rolled to form a rail blank. The heating temperature of the bloom means the temperature at the center of the cross section perpendicular to the longitudinal direction of the bloom. The heating temperature of the bloom can be measured by embedding a thermocouple in the center of the bloom. The heating temperature of the bloom can also be calculated by one-dimensional heat transfer solidification calculation based on the actual measurement value by the thermocouple and the heat pattern of the heating furnace. The heat transfer and solidification calculation uses the enthalpy method or the equivalent specific heat method.

[0127] [Reheating conditions in a heating furnace] Reheating in a heating furnace furthermore satisfies the following conditions: (Condition 3) The average heating rate HR1 in the temperature range from 50°C to 600°C of the bloom is set to 2.0 to 5.0°C / min. (Condition 4) The average heating rate HR2 in the temperature range where the bloom temperature is 700 to 900°C is more than 5.0 to 8.0°C / min. These conditions are explained below.

[0128] [(Condition 3) Average heating rate HR1] In steel, Si diffuses actively at temperatures higher than 900° C. However, the distribution state of Si in the bloom at temperatures below 900° C. affects the diffusion of Si above 900° C. Therefore, it is preferable to reduce the fluctuation of the distribution of Si in the bloom at temperatures below 900° C. to some extent.

[0129] In the bloom temperature range of 600°C or less, carbides are formed in the bloom. The interface between the carbide and the matrix becomes a diffusion path for Si. Therefore, if an appropriate amount of carbides of appropriate size are formed in the temperature range from room temperature to 600°C, a sufficient amount of interfaces between the carbide and the matrix are formed, and a sufficient amount of Si diffusion paths are formed. In this case, the fluctuation of the Si distribution in the bloom below 900°C can be suppressed to some extent.

[0130] If the average heating rate HR1 from room temperature to 600°C is less than 2.0°C / min, the generated carbide becomes excessively coarse. In this case, the interface between the carbide and the base material is insufficient. As a result, a sufficient amount of Si diffusion paths cannot be secured. Also, if the average heating rate HR1 exceeds 5.0°C / min, the bloom temperature exceeds the carbide generation temperature range (600°C or less) before a sufficient amount of carbide is generated. Therefore, the amount of carbide generated is insufficient, and the interface between the carbide and the base material is insufficient. As a result, a sufficient amount of Si diffusion paths cannot be secured.

[0131] If the average heating rate HR1 is 2.0 to 5.0 ° C / min, carbides of appropriate size are generated in sufficient quantities. In this case, the interface between the carbide and the matrix is ​​formed in sufficient quantities. Therefore, the diffusion path of Si is sufficiently formed. As a result, the fluctuation of the distribution of Si in the bloom below 900 ° C can be suppressed to some extent.

[0132] [(Condition 4) Average heating rate HR2] In the temperature range of 700 to 900°C, the carbides in the bloom melt. As described above, Si diffuses actively above 900°C. However, the distribution state of Si in the bloom below 900°C affects the diffusion of Si above 900°C. Therefore, it is preferable to reduce the fluctuation of the distribution of Si in the bloom below 900°C to some extent.

[0133] When the average heating rate HR2 in the temperature range of 700 to 900 ° C is 5.0 ° C / min or less, the carbide in the bloom dissolves. However, because the heating rate is slow, C in the dissolved carbide may be regenerated as carbide. In this case, the regenerated carbide inhibits the diffusion of Si. Therefore, the fluctuation in the Si distribution is not eliminated and tends to remain as it is. As a result, the temperature exceeds 900 ° C while the localized fluctuation in the Si distribution remains in the bloom. In this case, even if the temperature exceeds 900 ° C and the diffusion of Si is promoted, the fluctuation in the Si distribution cannot be sufficiently eliminated.

[0134] Furthermore, if the average heating rate HR2 in the temperature range of 700 to 900°C exceeds 8.0°C / min, some of the carbides in the bloom do not completely dissolve and remain. In this case, some of the remaining carbides inhibit the diffusion of Si. Therefore, even in this case, the fluctuation in the Si distribution is not eliminated and tends to remain as it is. As a result, the temperature exceeds 900°C while the localized fluctuation in the Si distribution remains in the bloom. In this case, even if the temperature exceeds 900°C and the diffusion of Si is promoted, the fluctuation in the Si distribution cannot be sufficiently eliminated.

[0135] If the average heating rate HR2 is more than 5.0 to 8.0°C / min, the bloom temperature exceeds 900°C at a relatively early stage after the carbide melts. Therefore, the C-enriched region does not exist for a long time, and C diffuses and disperses early after the carbide melts. As a result, the fluctuation of the Si distribution is reduced to a certain extent at 900°C or less. As a result, the diffusion of Si is promoted after the temperature exceeds 900°C, and Si is easily dispersed uniformly.

[0136] The temperature of the bloom means the temperature at the center of the cross section perpendicular to the longitudinal direction of the bloom, as with the heating temperature described above. The temperature of the bloom can be measured by embedding a thermocouple in the center of the bloom. The heating temperature of the bloom can also be obtained by FEM analysis based on the actual measurement value by the thermocouple and the heat pattern of the heating furnace.

[0137] The average heating rate HR1 (°C / min) can be calculated by determining the time it takes for the bloom temperature to rise from room temperature to 600°C. Also, the average heating rate HR2 (°C / min) can be calculated by determining the time it takes for the bloom temperature to rise from 700°C to 900°C.

[0138] The bloom heated under the above reheating conditions is subjected to hot rolling to produce a rail-shaped preform (rail preform). In hot rolling, the temperature of the rail preform when it passes through the final pass is referred to as the final rolling temperature. The temperature when it passes through the final pass means the temperature of the rail preform when it passes through a rolling stand that performs the final reduction on the rail preform. The final rolling temperature can be measured, for example, by a thermometer installed on the exit side of the rolling stand that performs the final reduction.

[0139] If the final rolling temperature is less than 750°C, pearlite transformation starts immediately after the completion of hot rolling. In this case, the rail 1 cannot be hardened in the heat treatment after the rolling, and sufficient wear resistance cannot be obtained. On the other hand, if the final rolling temperature exceeds 1100°C, austenite grains become coarse in the rail preform after hot rolling. In this case, hardenability increases excessively. Therefore, bainite, which reduces wear resistance, is formed in the head surface portion 10A of the rail 1. As a result, sufficient wear resistance cannot be obtained in the rail 1. Therefore, the final rolling temperature is set to 750 to 1100°C.

[0140] Other hot rolling conditions are not particularly limited. In order to ensure the hardness of the head surface portion 10A of the rail 1, the reheating temperature of the bloom and the final rolling temperature are controlled as described above while performing groove rolling, which is a normal rail manufacturing process. For example, after rough rolling the bloom, intermediate rolling is performed over multiple passes using a reverse rolling mill, and then finish rolling is performed in multiple passes using a continuous rolling mill. During the final rolling of this finish rolling, the final rolling temperature is controlled within the above temperature range.

[0141] [(Step 3) Heat treatment step] The rail blank immediately after hot rolling is subjected to the next heat treatment (accelerated cooling). The equipment for performing the accelerated cooling is not particularly limited. For example, the accelerated cooling may be performed using a cooling device 20 shown in Fig. 8. Referring to Fig. 8, the cooling device 20 includes a plurality of injection nozzles 21 for injecting a refrigerant onto the head surface portion 10A, a supply path 210 for supplying the refrigerant to the plurality of injection nozzles 21, and a supply device 22 for supplying the refrigerant to the supply path 210.

[0142] The multiple injection nozzles 21 are arranged in the longitudinal direction of the rail preform 100 over the entire length of the rail preform 100. Note that the cooling device 20 may not arrange the multiple injection nozzles 21 in the longitudinal direction of the rail preform 100 over the entire length of the rail preform 100, but may arrange them only on a part of the rail preform 100. In this case, the cooling device 20 further includes a drive device that moves the rail preform 100 in the longitudinal direction during accelerated cooling. Even in this case, the entire length of the rail preform can be cooled continuously.

[0143] The multiple injection nozzles 21 are arranged to surround the rail head 10. The injection nozzles 21 inject the refrigerant toward the head surface portion 10A. The supply device 22 supplies the refrigerant to the supply path 210. The supply device 22 supplies the refrigerant to the supply path 210, and the refrigerant is injected from the injection nozzles 21 to accelerate cooling of the head surface portion 10A. The refrigerant is not particularly limited. The refrigerant may be compressed air (air), a mixed refrigerant (mist) of water and air, or water. A combination of these refrigerants may be used.

[0144] [Cooling conditions] In accelerated cooling, the following conditions are satisfied: (Condition 5) The cooling start temperature TS at the head outer surface 10S is set to 750°C or higher. (Condition 6) The average cooling rate CR over the head outer surface for 10 s is set to 2.0 to 20.0°C / sec. (Condition 7) The cooling end temperature TE at the head outer surface 10S is set to 500 to 660°C.

[0145] Here, the cooling start temperature TS means the temperature (°C) of the head outer surface 10S when accelerated cooling of the rail preform is started. In other words, the cooling start temperature TS means the temperature (°C) of the rail preform when the coolant starts to be sprayed onto the rail preform. The average cooling rate CR means a value (° C. / sec) obtained by dividing the difference between the cooling start temperature TS and the cooling end temperature TE by the cooling time. The cooling end temperature TE means the temperature (° C.) of the rail preform when cooling of the rail preform at the above-mentioned average cooling rate CR is completed. These conditions are explained below.

[0146] [(Condition 5) Cooling start temperature TS] If the cooling start temperature TS is less than 750°C, pearlite will be generated before the accelerated cooling starts. In this case, sufficient hardness will not be obtained in the head surface portion 10A. In addition, if the C content of the rail 1 is high, pro-eutectoid cementite will be generated if the cooling start temperature TS is less than 750°C. In this case, sufficient toughness will not be obtained in the rail 1. If the cooling start temperature TS is 750° C. or higher, accelerated cooling can be started at a temperature higher than the pearlite transformation start temperature and the pro-eutectoid cementite transformation start temperature. Therefore, by performing accelerated cooling up to the cooling stop temperature TE at the above-mentioned average cooling rate CR, an appropriate metal structure and hardness can be obtained in the rail 1.

[0147] [(Condition 6) Average cooling rate CR] If the average cooling rate CR is less than 2.0°C / sec, the pearlite lamellae formed in the head surface portion 10A become coarse. In this case, sufficient hardness cannot be obtained in the head surface portion 10A. On the other hand, if the average cooling rate CR exceeds 20.0°C / sec, bainite and martensite are excessively formed in the head surface portion 10A, and the pearlite area ratio becomes excessively low. If the average cooling rate CR is 2.0 to 20.0°C / sec, appropriate metal structure and hardness can be obtained in the head surface portion 10A.

[0148] [(Condition 7) Cooling stop temperature TE] If the cooling end temperature TE exceeds 660°C, the pearlite lamellae formed in the head surface portion 10A become coarse. In this case, sufficient hardness cannot be obtained in the head surface portion 10A. On the other hand, if the cooling end temperature TE is less than 500°C, bainite and martensite are excessively formed in the head surface portion 10A, and the pearlite area ratio becomes excessively low. If the cooling end temperature TE is 500 to 660°C, appropriate metal structure and hardness can be obtained in the head surface portion 10A.

[0149] By the above manufacturing method, the rail 1 satisfying features 1 to 4 is manufactured. EXAMPLES

[0150] The effect of the rail of this embodiment will be described more specifically with reference to an example. The conditions in the following example are one example of conditions adopted to confirm the feasibility and effect of the rail of this embodiment. Therefore, the rail of this embodiment is not limited to this one example of conditions.

[0151] Rails having the chemical compositions shown in Table 1 (Tables 1A to 1D) were manufactured.

[0152] [Table 1A]

[0153] [Table 1B]

[0154] [Table 1C]

[0155] [Table 1D]

[0156] In Table 1, "-" indicates that the content of the corresponding element is equal to or lower than the impurity level. In all test numbers, the O content was 0.0060% or less.

[0157] The rails of each test number were manufactured under the manufacturing conditions shown in Table 2 (Tables 2A and 2B).

[0158] [Table 2A]

[0159] [Table 2B]

[0160] Specifically, blooms were produced by continuous casting using molten steel. The central solid fraction (%) of the blooms at the start of soft reduction during continuous casting and the central solid fraction (%) at the end of soft reduction were as shown in Table 2. The reduction ratio during soft reduction was 2 to 5%. In addition, the reduction ratios when the central solid fraction exceeded 70% were all 40 to 70% of the reduction ratios when the central solid fraction was 70% or less.

[0161] The produced bloom was subjected to hot rolling. First, the bloom was reheated to 1000 to 1350° C. The average heating rate HR1 (° C. / min) and the average heating rate HR2 (° C. / min) were as shown in Table 2. The reheated blooms were subjected to hot rolling to produce rail preforms having a rail shape. The final rolling temperature was 750 to 1100°C for all test numbers.

[0162] The rail preform after hot rolling was subjected to heat treatment (accelerated cooling). The cooling device used was the one shown in Figure 8. The cooling start temperature TS (°C), average cooling rate CR (°C / sec), and cooling end temperature TE (°C) were as shown in Table 2.

[0163] Through the above manufacturing process, rails with each test number were manufactured.

[0164] [Evaluation test] The manufactured rails were subjected to the following evaluation tests. (Test 1) Pearlite area ratio measurement test on head surface (Test 2) Vickers hardness measurement test of head surface (Test 3) Si positive segregation measurement test (Test 4) Si negative segregation measurement test (Test 5) Abrasion resistance and damage resistance evaluation test Each test will be explained below.

[0165] [(Test 1) Measurement of pearlite area ratio on head surface] The pearlite area ratio of the head surface portion of the rail of each test number was measured based on the method described in the above-mentioned [Method for observing the metal structure of the head surface portion 10A]. The measurement results are shown in Table 3 (Table 3A and Table 3B). For each test number, the pearlite area ratio was 95% or more, and the remainder other than pearlite in the metal structure was one or more types selected from the group consisting of ferrite, cementite, bainite, and martensite.

[0166] [Table 3A]

[0167] [Table 3B]

[0168] [(Test 2) Vickers hardness measurement test of head surface] Based on the method described above in [Method of measuring Vickers hardness of head surface portion 10A], the Vickers hardness H1 at a depth of 1 mm, the Vickers hardness H10 at a depth of 10 mm, and the Vickers hardness H20 at a depth of 20 mm on the head surface portion of the rail of each test number were obtained. The obtained Vickers hardnesses H1, H10, and H20 are shown in Table 3.

[0169] [(Test 3) Si positive segregation measurement test] Based on the method described in the above [Method of measuring the Si positive segregation degree and the Si negative segregation degree in the head surface portion 10A], the Si positive segregation degree in the head surface portion 10A of each test number was obtained. The obtained Si positive segregation degrees are shown in Table 3.

[0170] [(Test 4) Si negative segregation measurement test] Based on the method described in the above [Method of measuring the Si positive segregation degree and the Si negative segregation degree in the head surface portion 10A], the Si negative segregation degree in the head surface portion 10A of each test number was obtained. The obtained Si negative segregation degrees are shown in Table 3.

[0171] [(Test 5) Abrasion resistance and damage resistance evaluation test] The abrasion resistance and damage resistance evaluation tests were carried out in the following manner. Two rails were prepared for each test number. The rail shape for each test number was 136 pounds (mass: 67 kg / m) and the length was 2 m.

[0172] The following rolling fatigue tests were carried out using the rails with each test number. [Rolling fatigue test] The rolling fatigue test was carried out as follows. In the rolling fatigue test, a rolling fatigue test machine shown in FIG. 3 was used. A wheel 2 of AAR type with a diameter of 920 mm was prepared. The radial load during the test was 300 kN, and the thrust load was 100 kN. The lubrication method used during the test was repeated water supply and drying. Specifically, water was supplied to the rail 1 for a certain period of time during the test, and then the water supply was stopped and the rail was dried for a certain period of time (water supply and drying). During the test, the number of repeated load applications using the wheel 2 was set to a maximum of 5 million times, and the cumulative passing tonnage was set to a maximum of 150 million tons.

[0173] [Method of evaluating damage resistance of rolling surfaces] The method for evaluating the number of cracks occurring on the rolling surface of the rail after the rolling fatigue test was as follows. The evaluation area was a range of 300 mm in the longitudinal direction of the rail 1 in the head corner portion 12 of the rail 1. A test specimen was taken from the evaluation area of ​​the rail 1 after the test, with the cross section parallel to the longitudinal direction and including the normal to the head outer surface 10S of the head corner portion 12 as the observation surface. The length of the observation surface in the longitudinal direction of the rail 1 was 300 mm. The observation surface was mirror-polished. The mirror-polished observation surface was visually inspected to confirm the presence or absence of cracks propagating from the head outer surface 10S in the depth direction of the rail 1. If a crack was detected, the length D (see Figs. 2A to 2C) of the crack in the depth direction from the contact surface (head outer surface 10S) was measured. The number of cracks with a length D of 500 μm or more was counted. The obtained number was regarded as the number of crack damage occurrences. The number of occurrences is shown in Table 3. If the number of crack damage occurrences was 5 or less, it was determined that excellent damage resistance was obtained.

[0174] [Method of assessing wear on rail head] The area of ​​1000 mm in the longitudinal direction of the rail 1 after the rolling fatigue test was determined as the evaluation area. The evaluation area was cut at 100 mm pitch in a cross section perpendicular to the longitudinal direction of the rail 1, and the shapes of the cross sections (a total of 11 cross sections) were recorded. The cross-sectional shapes perpendicular to the longitudinal direction of the test pieces of the rail 1 before the rolling fatigue test were also recorded in advance. The cross-sectional shapes of the rail 1 before the rolling fatigue test and each cross-sectional shape after the rolling fatigue test were compared, and the wear depth (mm) at the width center position of the rail 1 at the rail head 10 was measured for each of the 11 cross-sectional shapes after the rolling fatigue test. The maximum value of the obtained wear depth was determined as the wear amount (mm). The wear amount is shown in Table 3. It was determined that excellent wear resistance was obtained if the wear amount was less than 5.00 mm.

[0175] [Evaluation Results] Referring to Tables 1 to 3, the rails of test numbers 1 to 54 satisfied features 1 to 4. Therefore, the number of rails with crack damage was less than 5, and excellent damage resistance was obtained. Furthermore, the amount of wear was less than 5.00 mm, and excellent wear resistance was obtained.

[0176] On the other hand, in the test numbers 55 to 58, the central solid fraction of the bloom at the start of soft reduction in continuous casting was too high. Therefore, the degree of positive Si segregation was too high. As a result, the number of cracks that occurred was 5 or more, and the damage resistance was low.

[0177] In test numbers 59 and 60, the central solid fraction of the bloom at the end of soft reduction in continuous casting was too low. Therefore, the degree of positive Si segregation was too high. As a result, the number of cracks that occurred was 5 or more, and the damage resistance was low.

[0178] In the test numbers 61 and 62, the average heating rate HR1 was too slow in the hot rolling process. Therefore, the degree of negative Si segregation was too low. As a result, the number of cracks that occurred was 5 or more, and the damage resistance was low.

[0179] In the test numbers 63 to 65, the average heating rate HR1 was too fast in the hot rolling process. Therefore, the degree of negative Si segregation was too low. As a result, the number of cracks that occurred was 5 or more, and the damage resistance was low.

[0180] In the test numbers 66 and 67, the average heating rate HR2 was too slow in the hot rolling process. Therefore, the degree of negative Si segregation was too low. As a result, the number of cracks that occurred was 5 or more, and the damage resistance was low.

[0181] In the test numbers 68 and 69, the average heating rate HR2 was too fast in the hot rolling process. Therefore, the degree of negative Si segregation was too low. As a result, the number of cracks that occurred was 5 or more, and the damage resistance was low.

[0182] In the test numbers 70 and 71, the cooling start temperature TS of the accelerated cooling in the heat treatment process was too low. Therefore, sufficient hardness was not obtained in the head surface portion 10A. As a result, the number of cracks that occurred was 5 or more, and sufficient damage resistance was not obtained. Furthermore, the wear amount was 5.00 mm or more, and sufficient wear resistance was not obtained.

[0183] In test numbers 72 and 73, the average cooling rate CR of the accelerated cooling in the heat treatment process was too slow. Therefore, sufficient hardness was not obtained in the head surface portion 10A. As a result, the number of cracks that occurred was 5 or more, and sufficient damage resistance was not obtained. Furthermore, the wear amount was 5.00 mm or more, and sufficient wear resistance was not obtained.

[0184] In test numbers 74 and 75, the average cooling rate CR of the accelerated cooling in the heat treatment process was too fast. Therefore, in the metal structure of the head surface portion 10A, the pearlite area ratio was less than 95%, and the remainder was bainite. As a result, the number of cracks that occurred was 5 or more, and sufficient damage resistance was not obtained. Furthermore, the wear amount was 5.00 mm or more, and sufficient wear resistance was not obtained.

[0185] In test numbers 76 and 77, the cooling stop temperature TE was too low. Therefore, in the metal structure of the head surface portion 10A, the pearlite area ratio was less than 95%, and the remainder was bainite and martensite. As a result, the number of cracks that occurred was 5 or more, and sufficient damage resistance was not obtained. Furthermore, the wear amount was 5.00 mm or more, and sufficient wear resistance was not obtained.

[0186] In the test numbers 78 and 79, the cooling end temperature TE was too high. Therefore, sufficient hardness was not obtained in the head surface portion 10A. As a result, the number of cracks that occurred was 5 or more, and sufficient damage resistance was not obtained. Furthermore, the wear amount was 5.00 mm or more, and sufficient wear resistance was not obtained.

[0187] The embodiments of the present disclosure have been described above. However, the above-described embodiments are merely examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above-described embodiments, and can be implemented by appropriately modifying the above-described embodiments without departing from the spirit of the present disclosure. [Explanation of symbols]

[0188] 1 Rail 10A Head surface 10S Head outer surface

Claims

1. In mass percent, C: 0.80-1.20%, Si: 0.80-2.50%, Mn: 0.10-2.00%, P: 0.0250% or less, S: 0.0250% or less, Al: 0 to 1.0000%, N: 0 to 0.0200%, Cr: 0-1.00%, Mo: 0 to 0.50%, Co: 0-1.00%, B: 0 to 0.0050%, Cu: 0 to 1.00%, Ni: 0 to 1.00%, V: 0-0.200%, Nb: 0 to 0.0500%, Ti: 0 to 0.0500%, Mg: 0 to 0.0200%, Ca: 0-0.0200%, Rare earth elements: 0 to 0.0500%, Zr: 0 to 0.0200%, and The balance is Fe and impurities, In the metal structure of the head surface portion from the head outer surface to a depth of 20 mm, the pearlite area ratio is 95% or more and the Vickers hardness is 400 HV or more, In the head surface portion, The ratio of the maximum value of the Si concentration in the Si positive segregation zone to the Si concentration in the bulk region is more than 1.00 to 1.35; The ratio of the minimum Si concentration in the Si negative segregation zone to the Si concentration in the bulk region is 0.90 to less than 1.00; rail.

2. 2. A rail according to claim 1, Al: 0.0001-1.0000%, N: 0.0001-0.0200%, Cr: 0.01-1.00%, Mo: 0.01-0.50%, Co: 0.01 to 1.00%, B: 0.0001 to 0.0050%, Cu: 0.01 to 1.00%, Ni: 0.01-1.00%, V: 0.001-0.200%, Nb: 0.0001 to 0.0500%, Ti: 0.0001 to 0.0500%, Mg: 0.0001-0.0200%, Ca: 0.0001-0.0200%, Rare earth elements: 0.0001 to 0.0500%, and Zr: 0.0001 to 0.0200%; rail.

Citation Information

Patent Citations

  • Rail and method for manufacturing same

    WO2019189686A1

  • Rail, and method for manufacturing rail

    WO2020054339A1

  • Welded rail

    WO2022071007A1

  • Production of optical card

    JP1988023244A

  • Highly wear-resistant perlite rail

    JP3078461B2